Study on Transport Properties of Chitosan Membrane in Different Types of Electrolytes - Ni Nyoman Rupiasih; Made Sumadiyasa; I Ketut Putra; Ni Made Rasmini (Journal of Mathematical and Fundamental Sciences, 2018)
In this study, the electrical properties of chitosan membrane in different types of electrolytes were investigated by analyzing the current-voltage (I"‘V) curve. The membrane used was chitosan membrane 2%. The different electrolyte solutions used were KCl, HCl, MgCl2, CaCl2 and AlCl3 at concentrations of 0.025 M. The I-V experiments were done using a two-compartment cell, which contained two working electrodes made of platinum connected to a DC current source and two Ag/AgCl reference electrodes connected to a voltmeter. All experiments were conducted at an ambient temperature of 28.7 °C. Water uptake (hydrophilicity) and Fourier transform infrared (FTIR) measurements were also studied in this research. The I-V curves show the ohmic behavior of the membrane. The resistance of the membrane was higher in the electrolyte solutions with larger Stokes radii and lower in the electrolyte solutions with larger diffusion coefficients, except in the HCl solution. These results indicate that the I-V curve shapes are affected by the type of electrolyte solution used for the chitosan membrane transport. The hydrophilicity of the membrane was improved after exposure to the electrolyte solutions. The FTIR analysis revealed a new peak at about 677 cm-1, which indicates the formation of C-Cl groups in the used membranes.